THE EPIDEMIOLOGY OF HANSEN’S DISEASE IN THE MUNICIPALITY OF CARIRÉ – CEARÁ, FROM 2001 TO 2010. - Francisco Rosemiro Guimarães Ximenes 4 , Jurandi Pontes Carvalho Filho5; Benedita Tatiane Gomes Liberato; Francisco Rodrigues Martins; Adriano Ferreira Martins; Jurandi Pontes Carvalho Filho; Marcelo Gurgel Carlos da Silva (Revista Gestão & Saúde, 2013)
Hansen’s disease is an important public health problem, which has been attackingand physically and socially mutilating innumerous subjects. The study had as objective to perform an epidemiological and operational assessment of Hansen’s disease in the municipality of Cariré – Ceará, from an epidemiological, descriptive and temporal survey, with the notified cases in the period from January 1st 2001 to December 31st 2010, from the Information System on Diseases of Compulsory Declaration (Sistema de Informação de Agravos de Notificação - SINAN)database at Cariré’s Municipal Health Secretariat, with 116 cases residing in the municipality. It has been observed that in recent years there has been an increase in the number of new cases of Hansen’s disease, the incident rate and the prevalence coefficient, especially in the year 2010, due to greater active demand, improvement in diagnosis capacity and close contact assessment. Such findings are important, if we consider the presence of the hidden endemic. Therefore, requiring the monitoring of rates over time.